Structural, electrical and ferroelectric properties of NiTiO3 synthesized by citrate-gel method - Viet, Chu Duc; Nga, Nguyen Tuyet; Tho, Do Duc; Ngoc, Tran Vu Diem; Dung, Nguyen Van; Bac, Luong Huu (Vietnam Journal of Science and Technology, 2022)
We carried out the study on NiTiO3 synthesized via citrate-gel method. Structural characteristics were determined by  XRD and SEM. The impedance spectra analysis was used to elucidate the dependence of complex impedance values on temperature and frequency. The correlation between DC-conductivity and the inverse temperature values was presented and it complied with semiconductor behavior of Arrhenius type. The real dielectric constant, dielectric loss and  AC-conductivity values were reported as a function of frequency ranging from 1 kHz to 10 MHz. Conductivity was found to obey Jonscher’s power law of conductivity. The NiTiO3 samples showed the ferroelectric behavior at room temperature.